Alternative Paths to Social Transformation in Sub-Saharan Africa: A Case for Poverty Alleviation Programmes by the Poor - JUDE SSEMPEBWA; JACQUELINE NAKAIZA; RITAH N. EDOPU (African Journal of Governance and Development, 2014)
This paper reviews and synthesises the findings of studies on poverty alleviation in the DRC, Kenya, Mozambique, Rwanda and Uganda to respond to two questions: why have some poverty alleviation programmes been more successful than others? What lessons for policy reform may be drawn from both the successful and less successful programmes? The findings were that: poverty alleviation programmes were more successful where the targeted poor were involved in the definition of poverty; and that many poverty alleviation programmes were implemented among/for people who did not perceive themselves as poor, and these tended to be ineffective. The paper presents and synthesises these findings, with the conclusion that they demonstrate a case for an ideological paradigmatic shift in the political economy of poverty and social transformation in the global south – from relegating the poor as passive consumers of poverty alleviation programmes to appreciating them as partners in the design of the programmes